An Unusual Cause of Dysphagia: Live Leech in the Tongue Base - Osman Erdoğan; Onur İsmi; Yusuf Vayısoğlu; Mustafa Azizoğlu; Kemal Görür; Cengiz Özcan (Turkish Archives of Otorhinolaryngology, 2015)

(untitled)
Inhaled or ingested foreign bodies are relatively common causes of airway obstructions. They can be associated with significant morbidity and even mortality. Although various foreign bodies are aspirated or ingested, live leeches are rarely encountered. We reported a case of a live leech at the base of the tongue in an 18-year-old female patient with a history of unfiltered spring water drinking. We discussed the surgical technique and importance of anesthesia with this brief study.